2016
DOI: 10.1002/dta.2118
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal evaluation of the isotope ratio mass spectrometric data: towards the ‘isotopic module’ of the athlete biological passport?

Abstract: The detection of the abuse of pseudo-endogenous steroids (testosterone and/or its precursors) is currently based on the application of the steroid module of the World Anti-Doping Agency (WADA) Athletes' Biological Passport (ABP), implemented through ADAMS. Diagnostic metabolites are monitored for every athlete and statistically evaluated with a predictive Bayesian approach. In the case of suspicious samples, the data of the ABP are confirmed and the isotope ratio mass spectrometry (IRMS) test is activated. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Additionally, based on abnormal values or profiles, athletes can be targeted for traditional anti‐doping tests to detect prohibited substances or methods. Although the ABP was initially proposed to monitor haematological variables to primarily detect blood doping (haematological module), this approach will be also used to detect the misuse of growth factors and anabolic steroids . At present, the ABP is a key tool for carrying out target testing, especially in endurance sports disciplines .…”
Section: Athlete Biological Passportmentioning
confidence: 99%
“…Additionally, based on abnormal values or profiles, athletes can be targeted for traditional anti‐doping tests to detect prohibited substances or methods. Although the ABP was initially proposed to monitor haematological variables to primarily detect blood doping (haematological module), this approach will be also used to detect the misuse of growth factors and anabolic steroids . At present, the ABP is a key tool for carrying out target testing, especially in endurance sports disciplines .…”
Section: Athlete Biological Passportmentioning
confidence: 99%
“…[17] In other words, our confirmation capacity in much better than our capacity to detect suspicious samples at the screening level. In addition, recent studies have demonstrated that the delta values of a single individual have a much lower variability compared to the current parameters of the ABP, and that the evaluation of the absolute delta values or the delta-delta values relative to an ERC may improve the detection capacity of the method since the acceptance limits would be almost half of the current population based ones.…”
Section: Resultsmentioning
confidence: 98%
“…[17] If this is applied, this could eventually detect those synthetic preparations with delta values close to the endogenous values region. [18] To do so, the throughput of the current IRMS strategy must be improved, permitting the application of IRMS on a larger scale.…”
Section: Introductionmentioning
confidence: 99%
“…The stability of the delta values of the pseudoendogenous steroids, including the ERC necessary for their evaluation, could also be assessed if an evaluation of the delta values was made longitudinally as part of a module of the Athlete Biological Passport (ABP) as we suggested recently …”
Section: Discussionmentioning
confidence: 99%